Tantangan dan Strategi Mahasiswa Muslim dalam Menjalankan Ibadah: Studi Kualitatif terhadap Pemahaman Fiqih Praktis - Faizin, M.; Agustin, Adithya; Nikmah, Nurul Hidayatun; Aisi, Rihhadatul; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to identify and analyze the challenges faced by Muslim university students in maintaining the consistency of their religious practices, particularly the five daily prayers, amidst demanding academic routines and campus activities. It also explores the strategies employed by students to remain disciplined in worship and highlights the importance of practical fiqh understanding in their daily lives. This research uses a descriptive qualitative approach, with in-depth interviews conducted among students of UIN Sulthan Thaha Saifuddin Jambi from various academic programs, particularly those in their early semesters. The findings reveal that students often encounter challenges such as time conflicts between class schedules and prayer times, limited access to adequate prayer facilities, fatigue, and the tendency to procrastinate worship. Nevertheless, the participants demonstrate a strong commitment to performing their religious duties by implementing strategies such as personal time management, using prayer reminder applications, carrying portable prayer equipment, and locating nearby prayer spaces. They also emphasize the critical role of practical fiqh knowledge, such as how to pray in non-ideal circumstances, combining (jama') prayers, and performing tayammum, in enabling them to fulfill their religious obligations effectively. The study recommends that universities be more proactive in providing sufficient worship facilities and strengthening religious mentoring through practical fiqh workshops. The findings are expected to serve as a foundation for developing campus policies that more effectively support the spiritual well-being of Muslim students.